Infeksi Anisakis sp. pada Layur (Trichiurus sp. ) di Pantai Selatan Kabupaten Purworejo - Eko Setyobudi; Senny Helmiati; Soeparno Soeparno (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The aims of this research were to know the prevalency, intensity and distribution of Anisakis sp. which infected hairtail (Trichiurus sp.) in the southern coast of Purworejo Regency. Samples were collected from fish landing-places in Jatimalang and Keburuhan, Purworejo Regency. Totally 276 fish were collected as samples during 4 months (September-December 2005). Every sampel was measured in total length and body weight. The examination of Anisakis sp. were conducted on body surface, body cavity, gut, liver, gonad, and muscle. Results of the research indicated that the Anisakis sp. infected various size of hairtail, with prevalency 62,68% and mean intensity of infection 3,30 individual/fish. Infected organs were body cavities (peritoneum), guts, gonads, livers, muscles, gills and pneumatocysts.